Answer:
see the attached table
Explanation:
We assume the formula of interest is ...
residual = (initial amount)(1 -k)^t . . . . . . assuming k is a positive number
Where T is the half-life, this formula can also be expressed as ...
residual = (initial amount)(1/2)^(t/T)
Then the relationship between k and T is ...
(1 -k)^t = (1/2)^(t/T)
or ...
1 -k = (1/2)^(1/T)
This lets us write k in terms of T as ...
k = 1 -(1/2)^(1/T)
and it lets us write T in terms of k as ...
log(1-k) = (1/T)log(1/2)
T = log(1/2)/log(1-k)
__
The attached spreadsheet table implements these formulas to compute T from k and vice versa. Formatting is in % and to four decimal places as required by the problem statement.